Modern waterproofing schemes and materials - Zhavarov Бейбут (Рroblems of engineering and professional education, 2023)
This article describes various types of waterproofing materials and schemes, technologies, application methods and water resistant measures when designing underground facilities and foundation. Geological features of Astana ground are described herein. Individual approach to waterproofing of underground facilities is mentioned herein. Main waterproofing requirements are shown in this Article.